Second language education context and home language effect: language dissimilarities and variation in immigrant students’ outcomes. - Figueiredo, Sandra (2018)
Heritage language speakers struggle in European classrooms with insufficient material provided for second language (SL) learning and assessment. Considering the amount of instruments and pertinent studies in English SL, immigrant students are better prepared than their peers in Romance language settings. This study investigates how factors such as age and home language can be used in the teaching environment to predict and examine the development outcomes of SL students in verbal reasoning and vocabulary tasks. Hundred and six Portuguese participants, SL learners, between 8 and 17 years old, were assessed in vocabulary frequency, verbal analogies and morphological extraction tasks. In alphabetic languages (Romance languages), immigrant students (in a SL learning situation) with a strong linguistic distance (a home language with a very different orthographic foundation) are expected to struggle in language learning in spite of being aware of strategies that can improve their skills. The storage and combination of morphemes can be a demanding task for individual speakers at different levels. Cognitive mapping is strongly based on linguistic features of L1 development. Results show that home language, not age, was a significant predictor of variation in student’s outcomes. Speakers of alphasyllabary languages (Indo-Aryan languages as L1) were the poorest performers, the ‘linguistic distance’ of their languages explaining the performance’ results